THE QUALITY OF RESEARCH GRANT PROPOSALS IN ENGLISH EDUCATION, LINGUISTICS, AND LITERATURE - Bambang Yudi Cahyono (Universitas Negeri Malang, 2016)
This article reports on the results of a research study on the quality of research grant proposals written by faculty members of the English Department of a university in East Java for the A-2 Competitive Grant Program managed by the Indonesian Directorate General of Higher Education (DGHE). This study is a descriptive research study and it describes the overall quality and the quality of the components of the research proposals. The results show that in general, most of the research proposals were of high quality. However, some of the proposals need moderate or minor revisions dealing with some aspects. Common shortcomings deal with incomplete referencing either as in-text citation or inclusion of the sources in the list of references. Other common weaknesses include the inaccuracy of research design and the unclear procedures for data analysis.